Investigation of Bending Effect on Long Period Fiber Gratings (LPFG) Refractive Index Sensitivity - Tan, Poh Seong (2015)
Improvement of refractive index sensitivity remained as high interest area for researchers working in fiber sensor including long period fiber gratings (LPFG). Various methods have developed to enhance the refractive index sensing like coating, etching, bending and etc. Recently bending method has successfully demonstrated by researcher through theory and simulated in different curves. However there is lack of experimental based data to demonstrate the effect of bending on LPFG refractive index sensitivity performance. During this project, investigation of bending effect on long period fiber gratings (LPFG) refractive index sensitivity was carried out to find the right method to form the bending on LPFG. From this study, practical results will able to show the right curve for bending LPFG and comparison of straight line LPFG was done to demonstrate the enhancement of refractive index sensitivity of bending LPFG. In addition, the number of gratings induced by arc-discharges on LPFG affected the refractive index sensitivity due to the length of LPFG under bending effect. It is concluded that the bending LPFG is more sensitive than LPFG in straight line.